Specification of the mammalian cochlea is dependent on Sonic hedgehog - Riccomagno, Martin M. (Cold Spring Harbor Laboratory Press, 2002)
Organization of the inner ear into auditory and vestibular components is dependent on localized patterns of gene expression within the otic vesicle. Surrounding tissues are known to influence compartmentalization of the otic vesicle, yet the participating signals remain unclear. This study identifies Sonic hedgehog (Shh) secreted by the notochord and/or floor plate as a primary regulator of auditory cell fates within the mouse inner ear. Whereas otic induction proceeds normally in Shh(−/−) embryos, morphogenesis of the inner ear is greatly perturbed by midgestation. Ventral otic derivatives including the cochlear duct and cochleovestibular ganglia failed to develop in the absence of Shh. The origin of the inner ear defects in Shh(−/−) embryos could be traced back to alterations in the expression of a number of genes involved in cell fate specification including Pax2, Otx1, Otx2, Tbx1, and Ngn1. We further show that several of these genes are targets of Shh signaling given their ectopic activation in transgenic mice that misexpress Shh in the inner ear. Taken together, our data support a model whereby auditory cell fates in the otic vesicle are established by the direct action of Shh.